MMS Measurements and Modeling of Peculiar Electromagnetic Ion Cyclotron Waves. Issue 21 (3rd November 2019) - Lee, Justin H.; Turner, Drew L.; Toledo‐Redondo, Sergio; Vines, Sarah K.; Allen, Robert C.; Fuselier, Stephen A.; Khotyaintsev, Yuri V.; Cohen, Ian J.; Mauk, Barry H.; Russell, Christopher T.; Pollock, Craig J.; Ergun, Robert E.; et al.
Abstract: Orbiting Earth's dayside outer magnetosphere on 29 September 2015, the Magnetospheric Multiscale (MMS) satellites measured plasma composition, simultaneous electromagnetic ion cyclotron waves, and intermittent fast plasma flows consistent with ultralow frequency waves or convection. Such flows can accelerate typically unobservable low‐energy plasma into a measurable energy range of spacecraft plasma instrumentation. We exploit the flow occurrence to ensure measurement of cold ion species alongside the hot particles—consisting of ionospheric heavy ions and solar wind He ++ —during a subinterval of wave emissions with spectral properties previously described as peculiar. Through application of the composition and multisatellite wave vector data to linear theory, we demonstrate the emissions are in fact consistent with theory, growing naturally in the He ++ band with sufficient free energy. Plain Language Summary: Electromagnetic ion cyclotron waves are a special class of plasma waves observed in space near Earth or in other magnetized plasmas. They emit electromagnetic energy near the local ion cyclotron frequencies, a relationship that has been studied extensively through theory. But investigations in space via satellite observations have been hindered by an observational problem. Spacecraft charge positive in sunlight due to interactions between sunlight and spacecraft surfaces. Because of this, positively charged ion species with very low energy are invisible to spacecraft plasma instruments. These invisible low‐energy ions are critical to measure to fully understand their effects on the wave emissions. Luckily, electric fields induced by sudden ambient magnetic field changes sometimes provide extra acceleration to these low‐energy ions, helping them enter plasma instrument apertures and be observed. We investigate the electromagnetic waves during one such acceleration interval and use comprehensive plasma instrument measurements to show waves thought to be peculiar are instead behaving consistent with theory. Exploring other times and regions of space under similar measurement conditions may improve our understanding of how the electromagnetic waves are generated and their evolution in space and time. Key Points: Convection flows enabled direct measurement of comprehensive plasma composition during observations of EMIC waves with peculiar properties Single‐spacecraft and multispacecraft measurements were applied to modeling and tests of linear kinetic theory The multiple heavy ion populations, even with low abundances, help sustain wave growth and explain the wave properties